2018
DOI: 10.1016/j.biortech.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic powder on membrane fouling mitigation and microbial community/composition in membrane bioreactors (MBRs) for municipal wastewater treatment

Abstract: This study aims to investigate the usefulness of magnetic powder addition in membrane bioreactors (MBRs) for membrane fouling mitigation and its effect on microbial community and composition. The comparison between the two MBRs (one with magnetic powder (MAS-MBR) and one without magnetic powder (C-MBR)) was carried out to treat synthetic municipal wastewater. Results showed that bioflocculation and adsorption of magnetic powder contributed only minimally to membrane fouling mitigation while the slower fouling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…The TMP in the M-MBR reached above 50 kPa until day 17 with an average fouling rate of TMP of 3.01 kPa d À1 , while the TMP in the M-MBR reached above 50 kPa until day 24 with an average fouling rate of TMP of 2.06 kPa d À1 . A similar result was reported by Liu et al5 The signicantly low fouling rate in the M-MBR indicates that integrating the magnetic eld unit into an MBR system is a promising method to alleviate the negative effects of membrane fouling, thereby prolonging the operation periods for MBRs.3.2 Zeta potential and particle sizes of mixed liquor colloid…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The TMP in the M-MBR reached above 50 kPa until day 17 with an average fouling rate of TMP of 3.01 kPa d À1 , while the TMP in the M-MBR reached above 50 kPa until day 24 with an average fouling rate of TMP of 2.06 kPa d À1 . A similar result was reported by Liu et al5 The signicantly low fouling rate in the M-MBR indicates that integrating the magnetic eld unit into an MBR system is a promising method to alleviate the negative effects of membrane fouling, thereby prolonging the operation periods for MBRs.3.2 Zeta potential and particle sizes of mixed liquor colloid…”
supporting
confidence: 67%
“…Magnetic bio-effect is considered to be the main factor in mitigating membrane fouling when magnetic powder is added in membrane bioreactors (MBRs) for membrane fouling mitigation. 5 Wang et al 6 reported that magnetic powder improved the dehydrogenase activity, enhanced the biomass growth, and exhibited good performance in the mitigation of membrane fouling. Chen et al 7 found that there are a variety of microbial species in the reactor and that the membrane fouling rate can be decreased by adding magnetic particles to the MBR.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic powder addition as a way to mitigate membrane fouling in MBRs was investigated by Liu, Liu, Li, et al (2018). Results showed that bioflocculation and adsorption of magnetic powder were only minimally effective at fouling mitigation, but the magnetic bio‐effect resulted in a slower fouling rate.…”
Section: Membrane Foulingmentioning
confidence: 99%
“…Considering the responsiveness of magnetic particles to the magnetic field, they can be easily separated, reactivated and reused, thus MAS process is cost-efficient. Recently, it also displayed great potential for mitigating membrane fouling in MBRs [8]. Wang et al [9] found that adding magnetic particle could effectively alleviate membrane fouling by encouraging microbes to produce less membrane foulants.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9] found that adding magnetic particle could effectively alleviate membrane fouling by encouraging microbes to produce less membrane foulants. Liu et al [8] found that magnetic bio-effect could significantly mitigate membrane fouling by reducing the amounts of macromolecules and pioneer bacteria from bulk sludge. Although MAS process has been extensively investigated for improving biomass growth and pollutants removal [10], the information on mitigating fouling in MBRs is still limited.…”
Section: Introductionmentioning
confidence: 99%